Decapod Crustacea collected by the NORFANZ Expedition: Galatheidae and Polychelidae - Ahyong, Shane T. (Zootaxa, 2007)
The present study reports on the squat lobsters (Galatheidae) and blind lobsters (Polychelidae) collected by the 2003 NORFANZ Expedition to the Lord Howe Rise, Norfolk, and West Norfolk Ridges in the northern Tasman Sea. Galatheids and polychelids, both typical components of the outer shelf and slope, were collected from 26 and 36 mostly deepwater stations, respectively. Polychelids were represented by five species in two genera; galatheids by 26 species in ten genera of which one genus and twelve species are new to science. Munida grieveae Vereshchaka, 2005, and M. gordoni Vereshchaka, 2005, both described from northeastern New Zealand, are synonymised with M. endeavourae Ahyong & Poore, 2004, and M. isos Ahyong & Poore, 2004, respectively, both described from eastern Australia.